2013
DOI: 10.1159/000350245
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cystatin C is Associated with Renal Function Recovery in Critically Ill Patients Undergoing Continuous Renal Replacement Therapy

Abstract: Purpose: Serum cystatin C (sCyC) has long been known as a reliable biomarker of renal injury. However, it remains to be tested whether sCyC is a reliable biomarker to predict renal recovery after continuous renal replacement therapy (CRRT). Methods: A retrospective analysis of patients admitted to a tertiary 18-bed intensive care unit from January 2008 to December 2011 was performed. Univariate and multivariate regression analyses were performed to test the independent predictors of renal recovery. The diagnos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
(25 reference statements)
1
12
0
1
Order By: Relevance
“…The level of CysC was observed to be relatively stable during continuous venovenous hemofiltration, suggesting that CysC can be used to monitor residual renal function during and immediately after RRT . Upon the initiation of RRT, serum CysC has been reported to be predictive of short‐term renal function recovery (P < 0.01), and it is not surprising that sCysC showed the greatest AUC value for predicting renal recovery in our study. Uchino et al found that UO was the most important predictor of successful discontinuation of RRT (AUC 0.808).…”
Section: Discussionsupporting
confidence: 52%
“…The level of CysC was observed to be relatively stable during continuous venovenous hemofiltration, suggesting that CysC can be used to monitor residual renal function during and immediately after RRT . Upon the initiation of RRT, serum CysC has been reported to be predictive of short‐term renal function recovery (P < 0.01), and it is not surprising that sCysC showed the greatest AUC value for predicting renal recovery in our study. Uchino et al found that UO was the most important predictor of successful discontinuation of RRT (AUC 0.808).…”
Section: Discussionsupporting
confidence: 52%
“…This suggests that the diagnostic performance of CysC in predicting renal recovery is clinically useful. However, it has been unclear whether serum CysC at cessation is an optimal indicator for successful weaning from CRRT, since prior studies focused on CysC levels at the time of CRRT initiation but not at its cessation [20]. Concerning this, our study found that serum CysC, at the time of CRRT cessation, was significantly predictive in the successfully weaned group during follow-up, with an AUC value of 0.739.…”
Section: Discussionmentioning
confidence: 59%
“…Therefore, serum CysC could be an optimal marker, not only for the diagnosis of chronic kidney disease, but also for predicting AKI [12]. Zhang et al [20] performed a retrospective study, and showed that higher serum CysC is associated with poor renal recovery and a longer dependence on CRRT in critically ill patients. This suggests that the diagnostic performance of CysC in predicting renal recovery is clinically useful.…”
Section: Discussionmentioning
confidence: 99%
“…CysC is a nonglycosylated basic peptide produced steadily and continuously by all nucleated cells, and its concentration is not affected by age, sex, and changes in muscle mass. The CysC level upon the initiation of RRT has been reported to be a predictor of short-term renal outcome (18). It is the only candidate functional marker of AKI that has been considered to replace creatinine (9).…”
Section: Discussionmentioning
confidence: 99%
“…decreased creatinine level upon the discontinuation of RRT was found to be a predictor of successful discontinuation (OR 0.996, P < 0.001); however, CysC was not studied, and the observed outcome was independence from dialysis for a short time period. The CysC level upon the initiation of RRT has been reported to be a predictor of short-term renal outcome (18). The association of CysC upon the discontinuation of RRT and long-term dialysis dependence has not been explored.…”
Section: Discussionmentioning
confidence: 99%